2007
DOI: 10.1096/fj.06-7815com
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cells induce arginase II in macrophages, thereby attenuating NO production

Abstract: In recent years it has become apparent that removal of apoptotic cells (AC) by professional phagocytes alters the macrophage phenotype. This change is characterized by attenuated proinflammatory cytokine expression and NO production, which mechanistically remained unexplained. With the intention to explore molecular mechanisms underlying reduced NO formation, we showed that NO production in IFNgamma-stimulated murine RAW264.7 macrophages exposed to AC but not to either necrotic or viable human Jurkat cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 39 publications
2
44
0
1
Order By: Relevance
“…Clearance of apoptotic cells may be one of those signals. Although argII expression is largely independent of Th2 cytokine signaling [53], it is strongly induced in macrophages during the incorporation of apoptotic bodies, where it plays a role in inhibiting classical macrophage activation [31]. In addition, post-Nb AAMs strongly up-regulated complement components such as C1q and C3a, which are known to increase the ability of lung macrophages to phagocytize and incorporate SPs and apoptotic granulocytes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Clearance of apoptotic cells may be one of those signals. Although argII expression is largely independent of Th2 cytokine signaling [53], it is strongly induced in macrophages during the incorporation of apoptotic bodies, where it plays a role in inhibiting classical macrophage activation [31]. In addition, post-Nb AAMs strongly up-regulated complement components such as C1q and C3a, which are known to increase the ability of lung macrophages to phagocytize and incorporate SPs and apoptotic granulocytes [38].…”
Section: Discussionmentioning
confidence: 99%
“…NO can also affect immune responses through its ability to regulate S-nitrosylation of several components of the apoptotic machinery (Okuda et al 1996, Melino et al 1997, Johann et al 2007, Shibata et al 2007). Apoptosis is an important process in lymphocyte homeostasis and maturation in the thymus, as well as in lymphocyte proliferation in the periphery.…”
Section: No and The Immune Responsementioning
confidence: 99%
“…Uptake of apoptotic cells does not induce an inflammatory response. Accordingly, macrophages upregulate arginase II after phagocytosis of apoptotic cells, which regulates NO production by NOS2 (Freire-de-Lima et al 2000, Johann et al 2007). Additionally, L-arginine, the substrate for NO production, can inhibit the programmed cell death of epimastigotes, either by NOS2-dependent production or by the activity of arginine decarboxylase, which produces polyamines that support parasite proliferation (Paveto et al 1995).…”
Section: The Dual Role Of No During T Cruzi Infectionmentioning
confidence: 99%
“…This is characterized by, among other factors, the release of anti-inflammatory mediators such as TGF-␤ or PGE 2 , combined with suppression of proinflammatory cytokine production (2-4). Furthermore, recognition of AC by macrophages attenuates the production of radicals such as NO (5) or superoxide, with the latter mechanism requiring activation of peroxisome proliferator-activated receptor-␥ (6). Recently, it was shown that sphingosine-1-phosphate (S1P) is released from AC via sphingosine kinase 2 (SphK2) to promote macrophage survival (4).…”
mentioning
confidence: 99%